Determinación del porcentaje de mortalidad de Malezas, en la interacción plástico Transparente – Radiación solar, en un agroecosistema inestable de Juanjuí - Del Aguila Rengifo, Cecilia (2014)
The project was carried out in Juanjui during two periods, the first from 26 August to 20 September 2013, the second from 18 November to 13 December 2013. The specific objectives were to identify the weeds in the field, assess the biomass, density, height of the weeds and the linear regression between them; locate strips of transparent plastic, on the ground, between the rows of corn, and determine the mortality of the weeds. The wording of the problem, how is the percentage of mortality of weeds in the transparent plastic interaction - solar radiation, located at different times after planting, in an agro ecosystem unstable, a corn field, in the Juanjui district?. The variables were: lnteraction clear plastic-solar radiation (independent variable) and the mortality percentage of weeds (dependent variable), taking the hypothesis to prove, if we clear plastic interaction- solar radiation on the ground, then the mortality percentage of weeds in the agro ecosystem unstable, in a corn field, presents statistical difference. Among the treatments were evaluated, plastic located on the same day of the planting (T1), Plastic located to 05 days after planting (T2), Plastic located to 1 O days after planting (T3), Plastic located 15 days after planting (T4), Plastic located 20 days after planting (T5), more of a witness without coverage (T6). The conclusions were: in the identification of the weeds in the two campaigns will be found fifteen (15) genres, including Eleusine indica, Cyperus rotundus, Scyrpus comunis, Cortadeira sp, Gynerium saggitattum, Euphorbia hypericifolia, Phyllantus neruri, Urtica dioica, Chenopodium sp, Commelina sp, Portulaca dioica, Talinum paniculatum, Plantago major, Hura crepitans, Tessaria integrifolia, etc. The weeds mortality %, the two campaigns, ANVA presentad high significance in the treatments; the Duncan proof in the first campaign, the T4 introduced the 100% mortality, reportad with data processed 10.05. The witness, (T6) without coverage of transparent plastic, had the lowest value with 0% mortality reportad with transformad data to one (1 ). In Duncan's test to the data of the second campaign, the T3 was superior numerically, with statistical similarity to all the treatments with coverage. Key words: linear regression, weeds mortality.